Promoting systems thinking at the MENA region’s first WEF Nexus Masterclass and Advanced School - CGIAR Initiative on NEXUS Gains (CGIAR, 2024)
Participants of the first Water–Energy–Food (WEF) Nexus online Masterclass and in-person Advanced School for the Middle East and North Africa region share how the courses have benefited them.